P222 Epidemiology of Candida emia at level-1 trauma care cent er in North India. (20th September 2022) - Kiro, Vandana; Sharad, Neha; Shrivastava, Smriti; Varma, Sharin; Ningombam, Aparna; Mathur, Purva
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM: Objective: Patients affected by trauma who get admitted to critical care units experience prolonged hospitalization and thereby acquire several infections. This retrospective observational study was done from 2014 to 2021 to observe Candida emia affecting this population. A total of 4816 patients admitted with traumatic injuries and hospitalized for treatment at ICU in our 190 bedded Level-1 Trauma center underwent this study. Methods: Paired blood samples were collected from patients showing signs of sepsis and incubated and monitored regularly by the BacT/ALERT system (bioMe´rieux In C., Marcy l'Etoile, France). All the positive signal samples exhibiting budding yeast cells on Gram stain were subcultured on Chrome agar and Sabouraud dextrose agar. Pure growths obtained were subjected for identification and susceptibility by MALDI-TOF and VITEK 2 system. Results: Out of the 4816 patients, 61 were affected by Candida emia. Out of 61, the maximum was in the age group of 31-40 years (19.7%). Male preponderance (50/61, 82%) was exhibited compared to females. To ascertain Candida emia, samples collected were blood (63/66, 95.5%) and CVP tip (3/66, 4.5%). Candida emia was primarily observed in patients who suffered major orthopedic trauma (14/61, 21.2%). A total of 66 Candida species were isolated from samples of these patients. Out of these, Candida tropicalis (43.9%) was the most common, followed by C. parapsilosis (22.7%), C. albicans (21.2%), C. haemulonii (4.5%), C. glabrata (3%), C. rugosa (3%), and C. guilliermondii (1.5%). Concerning antifungal resistance, fluconazole resistance was 16.6% (11), flucytosine 1.5% (1), amphotericin B 6% (4), and micafungin 3% (2). Voriconazole was resistant to none but intermediate to 12.1% (8), caspofungin was intermediate to 3% (2), and resistant to none. A total of 47% (31/61) of patients succumbed to their injuries which were observed highest in the age group of 61-70 years (8/61, 25.8%). The most common injuries that the deceased suffered were polytrauma (9/61, 29%) and blunt trauma abdomen (9/61, 29%). Maximum mortality was also observed in patients with Candidaemia due to Candida tropicalis (15/61, 48.3%). Conclusion: Candidaemia is usually fatal. Mortality due to Candidaemia increases in patients with severe traumatic injuries and added risk factors such as extremes of age, immunocompromised state, and broad-spectrum antibiotics. When compared to a similar study done in our center from 2009 to 2012 (3 years) on Candidaemia in ICU patients, the incidence was lower in our study (12.6% per 1000 ICU admissions vs 14.9% per 1000 ICU admissions), but the mortality rate was higher (47% vs 43.3%). Therefore, a watchful eye on early signs of sepsis, strict hospital infection control measures and antimicrobial stewardship may alter their outcome.